Comprehensive analysis of damage associated SNPs of MMP9 gene: A computational approach. (December 2018) - Bhatnager, Richa; Bhasin, Maheshwar; Dang, Amita S.
Graphical abstract: Highlights: MMP9 is a matrix metalloproteinase of Gelatinases family involved in the metabolism of collagen. Majority of SNPs are still uncharacterized in disease causing potential, hence become necessary to find deleterious one. In-silico analysis offer advantage over the lab based characterization because of their convenience, speed, and lower cost. 2 nsSNP, 7 UTRs SNPs & 13 splice site SNPs may have the potential to affect the structure, function and expression of MMP9. Abstract: Extracellular matrix is a dynamic meshwork of macromolecules that plays an important role in biological processes such as tissue remodeling and various developmental processes. Collagen is the chief component of ECM. Upon hydrolysis, it forms an irreversible left-handed helical structure which is further hydrolyzed by a specialized group of MMP family i.e. Gelatinases (MMP2 and MMP9). Present study was carried to figure out deleterious SNPs associated with MMP9 gene. Our results showed that two nsSNP (rs8125581 and rs41529445) that are present in catalytic domain are highly conserved and affect the protein structure and function.7 SNPs located in UTRs were found to alter miRNA seed region 13 SNPs of splice site were predicted to affect splice signals thereby affecting the post translational expression of MMP9. Most of the SNPs are still uncharacterized thereby present study provides a direction that can help to validate the relation between the altered expressions and functions of MMP9 protein in terms of disease susceptibility.